Assessment of Quality of Life in Diabetes and Hypertensive Patients Attending Tertiary Care Hospitals in Khammam Region - Nikhitha, Konda; Sai Kiran, Sikilambatla; Prasad, Meraboina; Eswaraiah, Maram Chinna (Journal of Pharmacy Practice and Community Medicine)
Background: Majority of people with chronic diseases especially having Hypertension and Diabetes have poor Quality Of Life to their therapeutic regimen and life style. It can also result in a variety of complications in body systems associated with undesirable metabolic conditions which affects the quality of life. Objectives: To inquire the effect of satisfaction of Hypertension by exploring Quality Of life in Hypertension and Diabetes. Methodology: A prospective cross sectional study was conducted for six months at tertiary care hospital, Khammam, Telangana. Sample of 200 patients were consented and interviewed to collect the information with an agreement to participate on the subject of socio demographics, physical, mental and behavioral characteristics using a structured questionnaire. Quality Of Life is measured by MINICHAL scale which contains two domains specifically mental domain and somatic domain with 17 questions. It as four potential answers, by way of the scores of 0=not at all, 1=yes, somewhat, 2=yes, a lot, 3=yes very much and sum the points ranging on or after 0-51 International Diabetes Federation indicates the best and worst levels of health, whereas last question be a sign of the overall agreement to participate the patient in study. Results: The scrutiny of this current study found that there is an average quality of life around 61.4% in hypertension and 44.4% in hypertension and diabetes. A significant correlation was also established by using chi square test, the p value is <0.001. Conclusion: This learning show, self-care is required to avoid the disease and as historical statements further more counselling is needed in patients to get better Quality Of Life.
Keywords: Chronic diseases; Hypertension; Diabetes; Quality of life; Mental domain; Somatic domain; MINICHAL; Significant Correlation.